2022
DOI: 10.1007/s11947-022-02769-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficacy of Microwave Blanching-cum-black Mould Inactivation of Whole Garlic (Allium sativum L.) Bulbs Using Ultrasound: Higher Inactivation of Peroxidase, Polyphenol Oxidase, and Aspergillus niger at Lower Processing Temperatures

Abstract: The freshly harvested whole garlic bulbs require the inactivation of peroxidase (POD), polyphenol oxidase (PPO), and Aspergillus niger . However, the conventional hot water blanching and modern pretreatment like ultrasound (US) and microwave (MW) cannot individually inactivate both the enzymes and Aspergillus niger to the desired levels without compromising the quality of the garlic due to either of the higher process temperatures (> 85 °C) or prolonged treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…The faster rate of POD inactivation compared to PPO inactivation indicates a higher resistance to ultrasound than that of PPO. This contrasts with the results reported by Kar and Sutar et al [ 46 ]. In Chen et al [ 24 ] who treated carrot juice with ultrasound, PPO activity decreased while POD activity increased, and PME activity showed an increase at 0.95 W/mL and a decrease at 2.38 W/mL and 3.80 W/mL.…”
Section: Resultscontrasting
confidence: 99%
“…The faster rate of POD inactivation compared to PPO inactivation indicates a higher resistance to ultrasound than that of PPO. This contrasts with the results reported by Kar and Sutar et al [ 46 ]. In Chen et al [ 24 ] who treated carrot juice with ultrasound, PPO activity decreased while POD activity increased, and PME activity showed an increase at 0.95 W/mL and a decrease at 2.38 W/mL and 3.80 W/mL.…”
Section: Resultscontrasting
confidence: 99%
“… 100 mg/L sodium hypochlorite solution, US + NaOCl on PPO activity became predominant especially after day 4 of storage, leading to a 2.31–fold reduction at the end of storage. [98] 6 Lettuce ε-polylysine POD, PPO Probe US; 20 kHz, 17, 23, 29 W/L, for 10 min at 20 °C.ε-polylysine solution (0.1–0.6 g/L) At 12 days storage period, the least POD and PPO activity was observed for US - ε-polylysine treatment. [99] 7 Potato L-Cysteine PPO Ultrasonic bath; 28 kHz; 100–500 W; time 2–10 min; 20 °C.…”
Section: Hurdle Approach- Us With Other Combined Technologiesmentioning
confidence: 99%
“… [98] explored the combined effect of US and chlorine dioxide (ClO 2 ) on the enzyme activities of minimally processed bok choy and it was observed that different enzymes were affected differently by the combined US and ClO 2 treatment. To illustrate, the activity of PPO was observed to be reduced after 6–9 days of storage, before and after when the enzyme activity was increased whereas the POD activity showed a significant reduction throughout the storage period when compared to the control.…”
Section: Hurdle Approach- Us With Other Combined Technologiesmentioning
confidence: 99%
“…TS has the advantage of achieving a considerable level of enzyme inactivation while maintaining the nutritional and sensory attributes of food products. It can achieve this because it is a non-thermal processing method that requires lower temperatures than conventional thermal processing methods to inactivate enzymes [ 130 ]. Additionally, TS can reduce processing time and energy requirements, which can lead to cost savings and improved efficiency [ 122 ].…”
Section: Effect Of Ts On Inactivation Of Enzymes In Foodmentioning
confidence: 99%